Sequence of U-Shaped Convolutional Networks for Assessment of Degree of Delamination Around Scribe - Rozsívalová, Veronika; Doležel, Petr; Štursa, Dominik; Rozsíval, Pavel (Atlantis Press, 2022)
The application of protective layers is the primary method of keeping metallic structures resistant to degradation. The measurement of the layer resistance to delamination is one of the important indicators of the protection quality. Therefore, ISO 4628 standard has been issued to handle and quantify the main coating defects. Here, an innovative assessment of degree of delamination around a scribe according to ISO 4628 standard has been practically realized. It utilizes an computer-driven deep learning-based method. The assessment method is composed of two shallow U-shaped convolutional networks in a row; the first for preliminary and the second for refined detection of delamination area around a scribe. The experiments performed on 586 samples showed that the proposed sequence of U-shaped convolutional networks meets the edge computing standards, provides good generalization capability, and provides precise delamination area detection for a large variability of surfaces.
Sekvence konvolučních sítí ve tvaru písmene U pro hodnocení stupně delaminace v okolí písma
Keywords: coil coating; delamination; semantic segmentation; deep learning; nátěrové hmoty; hluboké učení; delaminace